OPTIMALISASI PEMBELAJARAN MENULIS AKSARA JAWA PADA SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN BERDIFERENSIASI BERBASIS PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) DAN TEACHING AT THE RIGHT LEVEL (TaRL): Optimizing Javanese Script Writing Learning For Elementary School Students Through Differentiated Learning Based On Culturally Responsive Teaching (CRT) And Teaching At The Right Level (TaRL) - Priya Kusuma Bahari; Abdulkadir Rahardjanto; Tri Susilowati; Fina Liswati Rahayu (Jurnal Inovasi Kreativitas Pendidikan dan Pembelajaran, 2025)
This study aims to improve the learning outcomes of Javanese script writing among fourth grade students through the implementation of differentiated learning based on Culturally Responsive Teaching (CRT) and Teaching at the Right Level (TaRL) approaches. The main problem identified was the low learning outcomes of students, where only 42% of students reached the Criteria for Achievement of Learning Objectives (KKTP) in the aspect of writing Javanese characters and sandhangan. This condition is influenced by the use of conventional learning methods that do not accommodate the different characteristics, ability levels, and cultural backgrounds of students. This classroom action research (PTK) was conducted in two collaborative cycles with a lesson study approach on 28 fourth grade students of SDN Tlogomas 2 Malang City. Data were collected through observation, field notes, documentation, and learning outcome tests. The results showed that the application of differentiated learning with CRT and TaRL integration significantly improved student learning outcomes, the percentage of learning completeness increased to 75% in cycle II. This approach is also able to increase students' motivation, engagement, and cultural awareness. This finding confirms the importance of implementing culturally responsive learning and students' developmental level to optimize learning outcomes in local content subjects, especially local languages in primary schools.